2023
DOI: 10.1002/lio2.1029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cochlear size on electrically evoked auditory brainstem responses in deaf children

Abstract: Objectives To investigate the relationship between auditory pathway function and cochlear size in deaf children with a radiologically normal inner ear or Mondini malformation. Methods Thirty‐five deaf children without inner ear malformations (IEMs) and forty cases with Mondini malformation were included in this study. The electrically evoked auditory brainstem responses (EABRs) evoked by electrical stimulation at the round window niche (RWN) and round window membrane (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The software can also give postoperative feedback to visualize and perform a quality check of the insertion and lead management status. The product has shown success in selection of appropriate CI electrodes in pediatric inner ear malformations 7,8 . It has been proposed that the new version of the software may also be used for BONEBRIDGE placements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The software can also give postoperative feedback to visualize and perform a quality check of the insertion and lead management status. The product has shown success in selection of appropriate CI electrodes in pediatric inner ear malformations 7,8 . It has been proposed that the new version of the software may also be used for BONEBRIDGE placements.…”
Section: Discussionmentioning
confidence: 99%
“…The product has shown success in selection of appropriate CI electrodes in pediatric inner ear malformations. 7 , 8 It has been proposed that the new version of the software may also be used for BONEBRIDGE placements.…”
Section: Discussionmentioning
confidence: 99%
“…OTOPLAN has been utilized to measure the CDL and estimate the frequency allocation map, assisting in selecting the most fitting electrode array [50]. In pediatric CI surgery, it has been observed that the physiological function of the peripheral auditory system is influenced by the anatomical structure of the cochlea, with a larger cochlear size being associated with better auditory conduction function [51].…”
Section: Surgical Planningmentioning
confidence: 99%